2013
DOI: 10.1111/jvh.12045
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus surface protein mutations clustered mainly in CTL immune epitopes in chronic carriers: results of an Iranian nationwide study

Abstract: Mutations within the coding region of hepatitis B surface antigen (HBsAg) have been found naturally in chronic carriers. To characterize the mutations of HBsAg from Iranian chronic carriers who were vaccine and/or medication naive. The surface genes from 360 patients were amplified and directly sequenced. The distribution of amino acid substitutions was classified according to different immune epitopes of the surface protein. All isolates belonged to genotype D. 222 (61.6%) of 360 patients contained at least o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 42 publications
(50 reference statements)
3
21
1
Order By: Relevance
“…This finding was in agreement with the results of other studies, especially in genotype D-infected patients [22,56]. In our study group, nearly half of the mutations (44.3%) occurred in the CTL epitope, suggesting a narrowly focused immune selection pressure at a hot spot position.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This finding was in agreement with the results of other studies, especially in genotype D-infected patients [22,56]. In our study group, nearly half of the mutations (44.3%) occurred in the CTL epitope, suggesting a narrowly focused immune selection pressure at a hot spot position.…”
Section: Discussionsupporting
confidence: 83%
“…De Maddalena et al [13] reported a significantly higher intragenotypic distance in genotype D than genotypes A and G, especially at the ‘a' determinant. Thus, it can be suggested that what is already known about the higher affinity of genotype D for mutations in the pre-C region can also be true for other regions [22,23]. This hypothesis is reinforced by the results of our study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, analysing partial genes instead of the full-length genome can sometimes lead to false epidemiological signals from distant geographical regions. For instance, Khedive et al [56] analysed 681 bp of isolated strains from HBV carriers in Iran and reported five strains with HBV subgenotypes D5 and D8, which is inconsistent with the known geographical distribution of subgenotypes. According to all epidemiological studies from Iran, D1 is the most frequent subgenotype of HBV, followed by a minor population of D2.…”
Section: Introducing "Hbv Subgenotyping Guidelines"mentioning
confidence: 86%
“…13 A majority of mutations of up-and downstream of MHR in different studies were found to be potentially responsible for vaccine breakthrough and HBsAg undetectability which unpredictably were found to be located within the known CTL epitopes of surface protein. 15,16 Mutations that abrogate recognition of a viral epitope by class Irestricted CTL contribute to viral persistence in a subset of patients with chronic HBV infection who express a narrow repertoire of anti-HBV CTL responses. Thus, viral mutations in CTL epitopes were able to evade cellular immunity and contribute to persistency.…”
Section: Discussionmentioning
confidence: 99%